Attentional Focus and swim speed in expert swimmers - Stoate, I.; Wulf, G. (International Journal of Sports Science and Coaching, 2011)
The study examined the effects of attentional focus on swim speed in expert swimmers. Thirty trained swimmers who had been competing for an average of ten years swam 3 lengths of a 25-yard pool, with oneminute breaks between lengths, in each of three conditions: external focus (instructed to focus on "pushing the water back"), internal focus ("pulling your hands back") and control condition (no instructions). Swim times were similar in the control and external focus conditions, but significantly slower in the internal-focus condition. Along with the results of Freudenheim et al., this study suggests that optimal focus of attention changes with practice/expertise: Whereas intermediate swimmers in the study by Freudenheim et al. benefited from the instructions to focus on pushing the water back, relative to no instructions, this was not the case for the experts in the present study. Directing the attention of novices and moderately-skilled swimmers externally - that is, to a higher level of control than that adopted by them spontaneously or as a consequence of instructions - is typically beneficial. Yet, for experts who have already learned to monitor their actions at a high level, instructions to focus externally may be superfluous. The above statement is based on the author`s premise that in swimming "a hierarchy of action goals" may involve "winning a competition", "swimming fast", "pushing water back", and "correct hand position".